Desarrollo financiero y crecimiento económico: Una visión crítica. - FitzGerald, V (Universidad de La Rioja, 2007)
Financial development involves the establishment and expansion of institutions, instruments and markets that support the investment and growth process. This article shall set out the theory and empirics on the relationship between financial development and economic growth--which underpin the "new standard model" of financial reform in developing countries--and examine the growing empirical evidence that suggests that this relationship is not so close or as unidirectional as is usually supposed, and does not provide a sound evidential basis for the prescriptions of the new standard model. Moreover, it shall tackle with two central issues in more detail: the effect of financial reform on savings and investment; and the consequences for macroeconomic stability. It shall finally offer some policy implications of the arguments and evidence presented.